A high incidence of disease flares in an open pilot study of infliximab in patients with refractory inflammatory myopathies. Issue 12 (13th February 2008) - Dastmalchi, M; Grundtman, C; Alexanderson, H; Mavragani, C P; Einarsdottir, H; Helmers, S Barbasso; Elvin, K; Crow, M K; Nennesmo, I; Lundberg, I E
Abstract : Objective: To investigate the effect of the tumour necrosis factor (TNF) blocking agent infliximab in patients with treatment-resistant inflammatory myopathies. Methods: A total of 13 patients with refractory polymyositis (PM), dermatomyositis (DM), or inclusion body myositis (IBM) were treated with 4 infliximab infusions (5 mg/kg body weight) over 14 weeks. Outcome measures included myositis disease activity score with improvement defined according to The International Myositis Assessment and Clinical Studies Group (IMACS), and MRI. Repeated muscles biopsies were investigated for cellular infiltrates, major histocompatibility complex (MHC) class I and II, TNF, interleukin (IL)1α, IL6, high mobility group box chromosomal protein 1 (HMGB-1), interferon γ (IFNγ), myxovirus resistance protein A (MxA) and membrane attack complex (MAC) expression. Type I IFN activity was analysed in sera. Results: Nine patients completed the study. Three patients discontinued due to adverse events and one due to a discovered malignancy. Three of the completers improved by ⩾20% in three or more variables of the disease activity core set, four were unchanged and two worsened ⩾30%. No patient improved in muscle strength by manual muscle test. At baseline, two completers had signs of muscle inflammation by MRI, and five at follow-up. T lymphocytes, macrophages, cytokine expression and MAC deposition in muscle biopsies were still evident after treatment. Type I IFN activity was increased after treatment. Conclusions: Infliximab treatment was not effective in refractory inflammatory myopathies. In view of radiological and clinical worsening, and activation of the type I IFN system in several cases, infliximab is not an alternative treatment in patients with treatment-resistant myositis.